The globalisation in the clothing sector and its implications for work organisation: a view from the Portuguese case - Moniz, António Brandão (2008)
The clothing sector in Portugal is still seen, in many aspects as a traditional sector with some average characteristics, such as: low level of qualifications, less flexible labour legislation and stronger unionisation, very low salaries and low capability of investment in innovation and new technology. Is, nevertheless, a very important sector in terms of labour market, with increased weight in the exporting structure. Globalisation and delocalisation are having a strong impact in the organisation of work and in occupational careers in the sector. With the pressure of global competitiveness in what concerns time and prices, very few companies are able to keep a position in the market without changes in organisation of work and workers. And those that can perform good responses to such challenges are achieving a better economical stability. The companies have found different ways to face this reality according to size, capital and position. We could find two main paths: one where companies outsource a part or the entire production to another territory (for example, several manufacturing tasks), close and/or dismissal the workers. Other path, where companies up skilled their capacities investing, for example, in design, workers training, conception and introduction of new or original products. This paper will present some results from the European project WORKS – Work organisation and restructuring in the knowledge society (6th Framework Programme), focusing the Portuguese case studies in several clothing companies in what concern implications of global context for the companies in general and for the workers in particular, in a comparative analysis with some other European countries.